Sensitivity of energy system investments to policy regulation changes: Too many, too fast?. (August 2018) - Bondarev, Anton; Weigt, Hannes
Abstract: In this paper we argue, that the interaction of energy policy regulations in the European electricity sector may be described by the slow-fast class of dynamical systems. Such systems may exhibit drastic changes in their dynamics known as bifurcations; one important being the so called blue sky catastrophe. Once reaching such a state, the slow system becomes unresponsive to the changes in the fast system. For the energy-policy nexus this translates into the energy system becoming unresponsive to policy interventions leading to a freeze in the system dynamics. Application of this result allows us to argue that caution is needed when updating economic policies to achieve a faster transition towards a low carbon energy supply structure. To avoid this risk the policy design should be aimed at long term incentive structures with less frequent but more consistent interventions. Abstract : Highlights: Recent trends in EU energy policy are explored. The energy-policy system is represented as a slow-fast system. Such systems may generically exhibit the blue sky catastrophe. The energy-policy system then becomes unresponsive to policy interventions. This calls for less frequent but more comprehensive energy policy reforms.